2011
DOI: 10.5897/ajmr10.717
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to -lactams of human and veterinary Salmonella isolates in Egypt and Algeria

Abstract: Seventy six non-typhoid Salmonella were isolated from both human and poultry in Egypt and Algeria and tested for their antibiotics resistance. The incidence of multiple antibiotics resistance was high. To study -lactams resistance mechanisms, double disk synergy test (DDST) with and without cloxacilline was used, results revealed the production of extended spectrum -lactamases (ESBLs) and cephalosporinase in seven and one human Egyptian isolates, respectively. The seven ESBL isolates were identified as Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…MDR Salmonella serovars were previously isolated from Egypt [ 65 , 66 , 67 , 68 , 69 ]. Traditional intervention methods for combating Salmonella have not been able to solve the dilemma of food quality and food safety [ 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDR Salmonella serovars were previously isolated from Egypt [ 65 , 66 , 67 , 68 , 69 ]. Traditional intervention methods for combating Salmonella have not been able to solve the dilemma of food quality and food safety [ 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, all the tested bacteria were identified as MDR because they resisted at least one antibiotic within more than three different classes. MDR Salmonella have been isolated previously from Egypt ( Abdelhakim et al, 2011 ; Abdel-Maksoud et al, 2015 ; Mahmoud et al, 2018 ; Merwad and Abdel-Haliem, 2018 ; Esmael et al, 2021b ; Abd-Elghany et al, 2022 ). In Egypt there are no boundaries on antibiotic remedies and antibiotics can be acquired easily without any medical prescription from drugstores and pharmacies ( Sobhy et al, 2012 ; Sabry et al, 2014 ; Awad et al, 2016 ; Esmael et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, high prevalence of AMR genes of non-typhoid Salmonella isolates to tetracycline and chloramphenicol was also detected [55]. A total of 76 non-typhoid Salmonellae were isolated from human and poultry in Egypt and Algeria and the isolates showed high incidence of cephalosporin's resistance [56]. A recent work of Eissa et al [12] demonstrated that patients with typhoid fever showed resistance to combined treatment with ciprofloxacin and Cefotax.…”
Section: Drug Resistancementioning
confidence: 99%